2023
DOI: 10.5530/ijper.58.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Lipid Metabolic Profiles by Trigonelline a Bioactive Compound of Trigonella Foenum-graecum in Alcohol Induced Albino Rats

Meesala Guru Sekhar,
Kondeti Ramudu Shanmugam,
Kanchi Siva Prasad
et al.

Abstract: Aim: Alcoholism leads to heart diseases, lung diseases and liver disorders. Alcoholism impairs heart homeostasis and causes cardio vascular diseases. The current investigation was carried out to know the hypolipidemic effect of Trigonelline (TG) a bioactive compound of Trigonella foenum-graecum (TGf ) in alcohol intoxicated rats. Materials and Methods: The rats were randomized into five groups and treatment was given as per the experimental protocol. The lipid metabolic profiles like Malondialdehyde (MDA), Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…Studies revealed that FS and BCS contain ample amounts of bioactive ingredients that strengthen their anti-diabetic potential by acting as strong antioxidants. Our results agree with the findings that FSs and BCSs possess beta-carotene, chlorogenic acid, caffeic acid, kaempferol, thymoquinone, saponins, and diosgenin (Hannan et al, 2007;Hameed et al, 2019;Laila et al, 2023;Sekhar et al, 2024). Our findings of antioxidants are correlated with the findings of Aslam et al (2024), who found that the antioxidant potential measured by DPPH scavenging activity and ferric-reducing activity is directly related to the concentration of BCS.…”
Section: Notesupporting
confidence: 93%
See 1 more Smart Citation
“…Studies revealed that FS and BCS contain ample amounts of bioactive ingredients that strengthen their anti-diabetic potential by acting as strong antioxidants. Our results agree with the findings that FSs and BCSs possess beta-carotene, chlorogenic acid, caffeic acid, kaempferol, thymoquinone, saponins, and diosgenin (Hannan et al, 2007;Hameed et al, 2019;Laila et al, 2023;Sekhar et al, 2024). Our findings of antioxidants are correlated with the findings of Aslam et al (2024), who found that the antioxidant potential measured by DPPH scavenging activity and ferric-reducing activity is directly related to the concentration of BCS.…”
Section: Notesupporting
confidence: 93%
“…Cholesterol levels of groups T3-T5 were reduced at the end of the study through the supplementation of FS and BCS. The current study showed a resemblance with the literature study performed by Chalabi et al (2019) and Sekhar et al (2024), in which diabetic group exhibited a significant decline (p < 0.05) in total cholesterol (TC) level treated with T. foenum gracum for 42 days in a dose-dependent manner. However, for N. sativa seeds, study findings were consistent with the study (Al-Logmani & Zari, 2011), in which BCS significantly (p < 0.001) increased levels of HDL-cholesterol and significantly (p < 0.001) reduced LDL-cholesterol in streptozotocin-induced diabetic models.…”
Section: Notesupporting
confidence: 85%